Contribution of nurses and midwives in the prevention of cervical cancer: a critical review - Vasic, Milica; Pazun, Vanja; Trbovic, Verica; Jezdimirovic, Danijela; Maricic, Milena (Education and Research in Health Sciences, 2024)
Introduction: Cervical cancer is a malignant disease that is the leading cause of cancer death in women. It develops through a series of precancerous epithelial changes called cervical intraepithelial neoplasia. Through the process of carcinogenesis, genetic and molecular changes transform cervical cells into invasive cancer, which can spread to surrounding tissue, lymph nodes, and other organs. Unfortunately, despite significant advances in the knowledge of pathogenesis and the development of early detection methods, cervical cancer has been and still remains one of the central and extremely complex area of gynecological oncology and represents a significant global health challenge. Objective:The main goal of the research was to analyse the contribution of nurses and midwives in the prevention of cervical cancer and to show more detailed considerations regarding different approaches and methods they use in their work, as well as their involvement in informing and raising awareness among women. Methods: The research methodology included a detailed search of relevant medical academic databases, with a precisely defined goal, which directed the research and enabled the identification of relevant information on the contribution of nurses and midwives in the prevention of cervical cancer. A qualitative analysis of the primary results was conducted to synthesize the data, highlighting dominant topics. Conclusion: Nurses have a significant responsibility in implementing preventive activities. Effective implementation of prevention programs, along with extensive public health education, can significantly contribute to reducing the incidences of cervical cancer. In order to enlarge their contribution and to improve the approach and methods of prevention, a well-coordinated cooperation between health professionals and political decision makers is necessary.